ANALISIS HUBUNGAN KODE-KODE SPBK (SISTEM PERINGKAT BAHAYA KEBAKARAN) DAN HOTSPOT DENGAN KEBAKARAN HUTAN DAN LAHAN DI KALIMANTAN TENGAH - Indah Prasasti; Rizaldi Boer; Muhammad Ardiansyah; Agus Buono; Lailan Syaufina; Yenni Vetrita (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2012)
Land and forest fire is one of causes ofland degradation in Central Kalimantan. Remote sensing dataapplications, especially READY-ARL NOAA and CMORPH data, are benefit forthe available climate observation data. The objectives of this research are: (1) to analyzis relationship between hotspots, FDRS and occurences of land and forest fire, and (2) to develop the estimation model of burned area from hotspot and FDRS codes. The result of this research showed that burned area can not be estimated by using number of hotspots. The drought code (DC) wich is one of FDRS codes has correlation with burned area. So, burned area can be estimated using drought code (DC) (R-sq = 58%) by using the following formula: Burned Area (Ha) = -62.9 + 5.14 (DC – 500).Keywords: land and forest fire, NOAA, CMORPH, hotspot